Some Properties For M – Homomorphism and M – Anti Homomorphism Over Q – Fuzzy M – HX Subgroups and its Level - Massa'deh, Mourad Oqla (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we define a new algebraic structure of a Q – fuzzy M – HX subgroup and the M – homomorphism and M – anti homomorphism of a Q – fuzzy M – HX subgroups. We discussed some properties characterizations of level subset of a Q – fuzzy M – HX subgroups of a M – HX group are given